2007
DOI: 10.1017/cbo9780511491160
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of the Unelected

Abstract: Unelected bodies, such as independent central banks, economic regulators, risk managers and auditors have become a worldwide phenomenon. Democracies are increasingly turning to them to demarcate boundaries between the market and the state, to resolve conflicts of interest and to allocate resources, even in sensitive ethical areas such as those involving privacy or biotechnology. This 2007 book examines the challenge that unelected bodies present to democracy and argues that, taken together, such bodies should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…We have indicated that the member states had different understandings of the policy implications of subsidiarity, but they also had conflicting conceptions about regional institutions and administrations, owing to the competing ideas of federalism versus inter-governmentalism, nationalism versus regionalism, and governance by governments versus governance by unelected arm's-length bodies (Vibert 2007). However, they all shared a common interest in making the increasing supranational EU competence more palatable and more democratic legitimate for their respective populaces.…”
Section: Making the Eu Competence More Democratic Through Subsidiaritymentioning
confidence: 94%
“…We have indicated that the member states had different understandings of the policy implications of subsidiarity, but they also had conflicting conceptions about regional institutions and administrations, owing to the competing ideas of federalism versus inter-governmentalism, nationalism versus regionalism, and governance by governments versus governance by unelected arm's-length bodies (Vibert 2007). However, they all shared a common interest in making the increasing supranational EU competence more palatable and more democratic legitimate for their respective populaces.…”
Section: Making the Eu Competence More Democratic Through Subsidiaritymentioning
confidence: 94%
“…It is influenced by the pluralist school of thought, according to which plural elites co-exist in largely separate spheres of society (Dahl 1961;Putnam 1977). The weakening of centralized political control is a concern of some authors writing in this vein (Peters & Pierre 2004;Dahlström et al 2011), while others take a more benign view of the effects of limiting majoritarian institutions (Vibert 2007;Cornell & Lapuente 2014). Professional pluralism is the version of pluralism most relevant to the Icelandic case, according to recent theorizing on the subject.…”
Section: Three Power Structure Modelsmentioning
confidence: 99%
“…Modern democracy relies not only on the principle of popular sovereignty but also on a set of independent institutions, which are neither directly elected nor controlled by "we, the people". 26 These unelected institutions are crucial because they enhance horizontal accountability and can oppose decisions taken by majority rule if these go against the liberal democratic pillar. Therefore, we should expect that these institutions will play a crucial role when it comes to striking down policies adopted by populists in power.…”
Section: Actorsmentioning
confidence: 99%